Optimization and fabrication of alginate scaffold for alveolar bone regeneration with sufficient drug release - Soleimani, Maryam; Asgharzadeh Salmasi, Ariyan; Asghari, Samaneh; Joneidi Yekta, Hamed; Kamyab Moghadas, Bahareh; Shahriari, Sheyda; Khandan, Amirsalar (Springer International Publishing Ag, 2021)
Bone tissues, with their porous structure and the crucial role of producing and releasing blood elements into the bloodstream, can act as a suitable candidate for drug delivery stations in all parts of the body. Making an appropriate osteoconductive scaffold with drug delivery is the basis of this study for designing such materials. In this research, bone scaffolds containing drugs and magnetite nanoparticles were designed and produced for bone tissue approaches. As a new class of treatment for bone defects or deformity, calcium silicate ceramics (CSC) have been able to attract a lot of attention among researchers as a viable solution. With the incorporation of metal oxides (like Fe3O4: magnetite nanoparticles; MNPs) into the base binary xCaO-ySiO(2)-MgO as well as the substitution of calcium ions, CSCs can be fabricated. In the current work, the scanning electron microscope (SEM) and X-ray diffraction (XRD) technique were used to determine the phase and morphology of the porous scaffolds for dental fracture. The observation shows that the compressive strength and elastic modulus increase from 0.9 to 1.76 MPa and 59 to 81 MPa, respectively. The SEM images proved that the porosity dimensions were reduced from sample 0 wt% to sample 15 wt% (From 85 to 70%). Also, the absorbance test was found to be increased from 0 to 15 wt% sample in the PBS immersion solution. The obtained results indicated that the samples with a maximum of 10 wt% MNPs might release the drug more comfortably, which can be reported as a suitable candidate for bone tissue application.
Keywords: Drug delivery; Pharmacological knowledge; Bone substitute; Tissue engineering; Natural polymer